Effect of airflow angle on abaxial surface deposition in air-assisted spraying - Xu, Shaoqing; Wang, Xiang; Li, Chao; Ran, Xiangkai; Zhong, Yuan; Jin, Ye; Song, Jianli (Frontiers in Plant Science, 2023)
Air-assisted sprayer is widely used in orchard pest and disease control. In air-assisted spraying, how to improve the deposition on the abaxial leaf surfaces is a problem to be solved. In this paper, the way to obtain well deposition on the abaxial leaf surfaces was investigated. The factors affecting the deposition on the abaxial surface was explored. Different angles of leaf, wind speed, velocities of platform and nozzle types were tested. The results showed that the abaxial surface coverage could significantly affected by the angle of leaf, the wind speed and the nozzle type. And the angle of leaf was the main factor among them. It mainly changes the exposed area of the abaxial surface in the wind field. Therefore, the exposure of the abaxial surface need to be improved in application. Then the exposure probability of the abaxial surface in different angles between the leaf and the airflow (α) was explored. The results showed that the relationship was well fitted the growth curve. The expo-sure probability would be over 95% when the α was greater than 5°. At last the conclusion was veri-fied through the field application. The deposition efficiency of the abaxial surface (DEAS) was calcu-lated. The experimental group achieved the DEAS of 49.9% and 109.3% in the middle and upper layer respectively. While DEAS were less than 30% when the airflow angle was not adjusted accord-ing to the theoretical value. Overall, the results can provide a reference for the adjustment of the wind field of air-assisted sprayers in applications.